Lipoprotein(a) Levels and Recurrent Vascular Events After First Ischemic Stroke. Issue 1 (January 2017) - Lange, Kristin S.; Nave, Alexander H.; Liman, Thomas G.; Grittner, Ulrike; Endres, Matthias; Ebinger, Martin
Abstract : Background and Purpose—: The association of elevated lipoprotein(a) (Lp(a)) levels and the incidence of cardiovascular disease, especially coronary heart disease and ischemic stroke, is well established. However, evidence on the association between Lp(a) levels and residual vascular risk in stroke survivors is lacking. We aimed to elucidate the risk for recurrent cardiovascular and cerebrovascular events in the patients with first-ever ischemic stroke with elevated Lp(a). Methods—: All patients with acute ischemic stroke who participated in the prospective Berlin C&S study (Cream & Sugar) between January 2009 and August 2014 with available 12-month follow-up data and stored blood samples were eligible for inclusion. Lp(a) levels were determined in serum samples using an isoform-insensitive nephelometry assay. We assessed the risk for the composite vascular end point of ischemic stroke, transient ischemic attack, myocardial infarction, nonelective coronary revascularization, and cardiovascular death with elevated Lp(a) defined as >30 mg/dL using Cox regression analyses. Results—: Of 465 C&S study participants, 250 patients were included into this substudy with a median National Institutes of Health Stroke Scale score of 2 (1–4). Twenty-six patients (10%) experienced a recurrent vascular event during follow-up. Among patients with normal Lp(a) levels, 11 of 157 subjects (7%) experienced an event at a median time of 161 days (interquartile range, 19–196 days), whereas in patients with elevated Lp(a) levels, 15 of 93 subjects (16%) experienced an event at a median time of 48 days (interquartile range, 9–194 days; P =0.026). The risk for a recurrent event was significantly higher in patients with elevated Lp(a) levels after adjustment for potential confounders (hazard ratio, 2.60; 95% confidence interval, 1.19–5.67; P =0.016). Conclusions—: Elevated Lp(a) levels are associated with a higher risk for combined vascular event recurrence in patients with acute, first-ever ischemic stroke. This finding should be validated in larger, multicenter trials. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01378468. Abstract : Supplemental Digital Content is available in the text.